Betti reaction enables efficient synthesis of 8-hydroxyquinoline inhibitors of 2-oxoglutarate oxygenases. Issue 84 (8th September 2015) - Thinnes, C. C.; Tumber, A.; Yapp, C.; Scozzafava, G.; Yeh, T.; Chan, M. C.; Tran, T. A.; Hsu, K.; Tarhonskaya, H.; Walport, L. J.; Wilkins, S. E.; Martinez, E. D.; et al.
Abstract : A Betti reaction was used for efficient generation of 2OG oxygenase inhibitors, including for KDM4 demethylases. Abstract : There is interest in developing potent, selective, and cell-permeable inhibitors of human ferrous iron and 2-oxoglutarate (2OG) oxygenases for use in functional and target validation studies. The 3-component Betti reaction enables efficient one-step C-7 functionalisation of modified 8-hydroxyquinolines (8HQs) to produce cell-active inhibitors of KDM4 histone demethylases and other 2OG oxygenases; the work exemplifies how a template-based metallo-enzyme inhibitor approach can be used to give biologically active compounds.